2010
DOI: 10.1189/jlb.1209793
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity and differential priming of circulating neutrophils in human experimental endotoxemia

Abstract: Neutrophils play an important role in host defense. However, deregulation of neutrophils contributes to tissue damage in severe systemic inflammation. In contrast to complications mediated by an overactive neutrophil compartment, severe systemic inflammation is a risk factor for development of immune suppression and as a result, infectious complications. The role of neutrophils in this clinical paradox is poorly understood, and in this study, we tested whether this paradox could be explained by distinct neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(187 citation statements)
references
References 38 publications
8
168
1
10
Order By: Relevance
“…Recent genomic and proteomic studies showed that PMN isolated from COPD patients displayed altered protein profiles and mRNA expression patterns (Langereis et al, 2011;Oudijk et al, 2005;Pillay et al, 2010). The main finding in the present study's noncontrol subjects was that the proteomes of their PMN had overexpression of S100A8, S100A12, PDI, GAPDH, and SOD, and under-expression of serpin B1, cronin 1A, actin isoforms, coactosin, and Rho GDPDI.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recent genomic and proteomic studies showed that PMN isolated from COPD patients displayed altered protein profiles and mRNA expression patterns (Langereis et al, 2011;Oudijk et al, 2005;Pillay et al, 2010). The main finding in the present study's noncontrol subjects was that the proteomes of their PMN had overexpression of S100A8, S100A12, PDI, GAPDH, and SOD, and under-expression of serpin B1, cronin 1A, actin isoforms, coactosin, and Rho GDPDI.…”
Section: Discussionsupporting
confidence: 57%
“…resting, primed, or activated); these changes are induced by cytokines and chemokines and are likely characterized by epigenetic changes (Oudijk et al, 2005). Phenotype changes not only alter the PMN shape and permit infiltration of injured tissues, but also make the cells functionally hyper-active in response to stimuli (Pillay et al, 2010;Sheppard et al, 2005). Neutrophil serine proteases (NSP), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the consequence of immature neutrophils in the bloodstream of tumor-bearing hosts is not entirely understood. Interestingly, immature neutrophils and neutrophil progenitor cellssome of which express KIT -are found in mouse models and patients with inflammation [69][70][71][72][73] .…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…Ward et al, 2010). The increase in peripheral banded neutrophils appears to be a response of the bone marrow to the widespread apoptosis of mature neutrophils in response to the cytokine storm of sepsis -however, while the newly released neutrophils are rapidly produced, they lack many of the functional aspects of fully differentiated neutrophils (Pillay et al, 2010). The increased number of banded neutrophils therefore may arise at the loss of fully differentiated and functional neutrophils.…”
Section: Immune Cell Dysfunction During Sirsmentioning
confidence: 99%